Variations in tooth size and arch dimensions in Malay schoolchildren - Hussein Khalid W.; Rajion Zainul A.; Hassan Rozita; Noor Siti Noor Fazliah Mohd (Sciendo, 2023)
To compare the mesio-distal tooth sizes and dental arch dimensions in Malay boys and girls with Class I, Class II and Class III malocclusions.